Tao The Watercourse way - "Watts, Alan" (New York, 1975)
According to Deepak Chopra, "Watts was a spiritual polymatch, the first and possibly greatest." Drawing on ancient and modern sources, Watts treats the Chinese philosophy of Tao in much the same way as he did Zen Buddhism in his classic The Way of Zen. Critics agree that this last work stands as a perfect monument to the life and literature of Alan Watts.
Keywords: Taoism China